The efficacy of a four-week intervention of complex training on power development in elite junior volleyball players - Watts, D. G.; Kelly, V. G.; Young, K. P. (Journal of Australian Strength and Conditioning, 2012)
The purpose of the study was twofold; firstly to evaluate the efficacy of a four week meso-cycle of complex training (CT) on strength and power characteristics in junior elite volleyball players (n=9 male, age=17.45±0.97) and secondly to evaluate any difference in the adaptations elicited from the intervention between athletes with high levels of reactive strength (HRS n=4) and low levels of reactive strength (LRS n=5). Pre and post power testing included a relative (absolute jump height - standing reach) measure of a spike jump reach (SJR) using a vaned jump and reach apparatus. Countermovement, squat and depth jumps were performed using a force plate and linear transducer to examine jump heights. A 1RM back squat was also tested pre and post-test to examine if any of the adaptations were due to an increase in strength. The four week intervention produced a 2.67%, 3.39% and 8.33% increase in relative measures of spike, countermovement and squat jumps respectively. These results illustrate that complex training is an effective means of increasing jump heights in a group of highly trained elite junior volleyball athletes. In a practical setting CT could be used as a taper leading into competition as it provides a training stimulus to increase jump height with a relatively smaller volume of strength training. see: https://www.researchgate.net/publication/229697906_THE_EFFICACY_OF_A_FOUR-WEEK_INTERVENTION_OF_COMPLEX_TRAINING_ON_POWER_DEVELOPMENT_IN_ELITE_JUNIOR_VOLLEYBALL_PLAYERS